2017
DOI: 10.1093/ajcp/aqx027
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Chain Reaction Human Papillomavirus (HPV) Detection and HPV Genotyping in Invasive Cervical Cancers With Prior Negative HC2 Test Results

Abstract: Our findings demonstrate that negative hrHPV testing on cervicovaginal cytology specimens in women later diagnosed with cervical carcinoma can be explained by the occurrence of truly HPV-negative carcinomas in more than half of patients. These results should be considered in the development of future cervical cancer screening guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 20 publications
6
19
0
1
Order By: Relevance
“…In this study, HPV-negative tumors represented a small percentage of cervical cancer (10%). These results are in keeping with previous reports, including a previous study conducted by our group with a smaller series of cervical cancer [15,28,29,30]. sensitivity of some HPV-testing methods when applied to formalin-fixed and paraffin-embedded tissues is likely to be the cause of the high prevalence of HPV-negative tumors observed in some studies [29].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, HPV-negative tumors represented a small percentage of cervical cancer (10%). These results are in keeping with previous reports, including a previous study conducted by our group with a smaller series of cervical cancer [15,28,29,30]. sensitivity of some HPV-testing methods when applied to formalin-fixed and paraffin-embedded tissues is likely to be the cause of the high prevalence of HPV-negative tumors observed in some studies [29].…”
Section: Discussionsupporting
confidence: 91%
“…The hrHPV and Pap tests together enhanced the predictive power of both screening tests in a complementary fashion. As previously demonstrated by our group and others, both the hrHPV and Pap tests have considerable false‐negative rates in the detection of high‐grade cervical lesions when used alone as a screening method. The histology follow‐up data in the current study also demonstrated that neither a negative hrHPV test result nor a negative Pap test result alone brought the 3‐year cumulative risk for high‐grade cervical lesions down to a considerably safe level.…”
Section: Discussionsupporting
confidence: 60%
“…It is important to determine whether these were negative or positive in surgical specimens. Recently, Tao et al demonstrated that humanpapillomavirus DNA was detectable in 44.3% of prior negative invasive cervical cancers (based on Hybrid Capture 2; Qiagen, Gaithersburg, Maryland, USA), using surgical specimens for polymerase chain reaction testing 14. In this study, humanpapillomavirus DNA was positive in 40.0% of pretreatment DNA genotype negative cervical cancer cases.…”
Section: Discussionmentioning
confidence: 49%
“…Moreover, a recent study found that 8–19% of cases were humanpapillomavirus negative, with an average of 14%, using cytology specimens 14. Our previous study also showed that the high risk human papillomavirus negative rate was 18.5% in pretreatment DNA genotype testing 6.…”
Section: Discussionmentioning
confidence: 67%